Genomic Profiling of Chinese Cervical Cancer Patients Reveals Prevalence of DNA Damage Repair Gene Alterations and Related Hypoxia Feature - Wen, Hao; Guo, Qin-Hao; Zhou, Xiao-Lan; Wu, Xiao-Hua; Li, Jin (Frontiers in Oncology, 2022)
Cervical cancer, the most common cancer in female genital tract, is responsible for 10-15% of cancer-related deaths in women worldwide. However, the genomic profiles of Chinese cervical cancer patients remain unclear. A total of 129 cervical cancer patients were enrolled in this study. To classify the clinical and molecular characteristics of cervical cancer, the genomic alterations of 618 selected genes were analyzed in the these patient samples, utilizing target next-generation sequencing (NGS) technology. Furthermore, the findings from the Chinese cohort were then compared with the data of Western patients downloaded from The Cancer Genome Atlas (TCGA) database, in terms of gene expression files, mutation data and clinical information. All studied patients had valid somatic gene alterations, and the most frequently mutated genes were PIK3C, TP53, FBXW7, ARID1A, ERBB2, and PTEN. The prevalence of genes, including TP53, KMT2C, and RET, was significantly different between the Chinese and TCGA cohort. Moreover, 57 patients (44.19%) with 83 actionable alterations were identified in Chinese cohort, especially in PI3K and DNA damage repair (DDR) pathways. After in-depth analysis of cervical cancer data from the TCGA cohort, DDR alteration was found to be associated with higher tumor mutation burden (TMB) (median mutation count: 149.5 vs 66, p<0.0001), and advanced stages (p<0.05). Additionally, DDR alteration, regardless of its function, was positively correlated with hypoxia feature and score. Moreover, patients with a high hypoxia score were positively correlated with a high abundance of mast cell resting, but lower abundance of CD8+ T cells and activated mast cell. Finally, CDHR5 was identified as the hub gene to be involved in the DDR-hypoxia network, which was negatively correlated with both the DDR alteration and hypoxia score. Overall, a unique genomic profiling of Chinese patients with cervical cancer was uncovered. The prevalent actionable variants would help promote the clinical management. Moreover, DDR alteration exerted significant influence on tumor microenvironment in cervical cancer, which could guide clinical decisions for the treatment. CDHR5 was the first identified hub gene to be negatively correlated with DDR or hypoxia in cervical cancer, which had potential effects on the treatment of immune checkpoint inhibitors (ICIs).